Understanding Children's Language and Speaking Development Education - Azhary Tanbusai; Khairina Nasution (PT FORMOSA CENDEKIA GLOBAL, 2023)
Language that includes understanding, expressing language through receptive language, literacy, and language development is referred to as this aspect of language development. Children evaluated him holistically, taking into account his intellectual accomplishments and all aspects of his personality. A writing study (Library Exploration) with a method of subjective exploration is the type of investigation used in the examination. A writing study is a review used to examine, peruse, record, and cycle research materials in order to gather data or a collection of library information. The specialist is directly connected to the text, which is one of the characteristics of this kind of research. One of the possibilities that youngsters need to develop early is their language potential. When the child looks at the pictures in the media drawing series right away, they become more interested in following the lessons and become more creative when it comes to telling stories.